Health-Care Utilization and Complications of Endoscopic Esophageal Dilation in a National Population - Abhinav Goyal; Kshitij Chatterjee; Sujani Yadlapati; Shailender Singh (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims Esophageal stricture is usually managed with outpatient endoscopic dilation. However, patients with food impaction or failure to thrive undergo inpatient dilation. Esophageal perforation is the most feared complication, and its risk in inpatient setting is unknown. Methods We used National Inpatient Sample (NIS) database for 2007-2013. International Classification of Diseases, 9th revision, Clinical Modification (ICD-9-CM) codes were used to identify patients with esophageal strictures. Logistic regression was used to assess association between hospital/patient characteristics and utilization of esophageal dilation. Results There were 591,187 hospitalizations involving esophageal stricture; 4.2% were malignant. Endoscopic dilation was performed in 28.7% cases. Dilation was more frequently utilized (odds ratio [OR], 1.36; p<0.001), had higher in-hospital mortality (3.1% vs. 1.4%, p<0.001), and resulted in longer hospital stays (5 days vs. 4 days, p=0.01), among cases of malignant strictures. Esophageal perforation was more common in the malignant group (0.9% vs. 0.5%, p=0.007). Patients with malignant compared to benign strictures undergoing dilation were more likely to require percutaneous endoscopic gastrostomy or jejunostomy (PEG/J) tube (14.1% vs. 4.5%, p<0.001). Palliative care services were utilized more frequently in malignant stricture cases not treated with dilation compared to those that were dilated. Conclusions Inpatient endoscopic dilation was utilized in 29% cases of esophageal stricture. Esophageal perforation, although infrequent, is more common in malignant strictures.